If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (U + 5)(u + -3) = 0 Reorder the terms: (5 + U)(u + -3) = 0 Reorder the terms: (5 + U)(-3 + u) = 0 Multiply (5 + U) * (-3 + u) (5(-3 + u) + U(-3 + u)) = 0 ((-3 * 5 + u * 5) + U(-3 + u)) = 0 ((-15 + 5u) + U(-3 + u)) = 0 (-15 + 5u + (-3 * U + u * U)) = 0 (-15 + 5u + (-3U + uU)) = 0 Reorder the terms: (-15 + -3U + 5u + uU) = 0 (-15 + -3U + 5u + uU) = 0 Solving -15 + -3U + 5u + uU = 0 Solving for variable 'U'. Move all terms containing U to the left, all other terms to the right. Add '15' to each side of the equation. -15 + -3U + 5u + 15 + uU = 0 + 15 Reorder the terms: -15 + 15 + -3U + 5u + uU = 0 + 15 Combine like terms: -15 + 15 = 0 0 + -3U + 5u + uU = 0 + 15 -3U + 5u + uU = 0 + 15 Combine like terms: 0 + 15 = 15 -3U + 5u + uU = 15 Add '-5u' to each side of the equation. -3U + 5u + -5u + uU = 15 + -5u Combine like terms: 5u + -5u = 0 -3U + 0 + uU = 15 + -5u -3U + uU = 15 + -5u Reorder the terms: -15 + -3U + 5u + uU = 15 + -5u + -15 + 5u Reorder the terms: -15 + -3U + 5u + uU = 15 + -15 + -5u + 5u Combine like terms: 15 + -15 = 0 -15 + -3U + 5u + uU = 0 + -5u + 5u -15 + -3U + 5u + uU = -5u + 5u Combine like terms: -5u + 5u = 0 -15 + -3U + 5u + uU = 0 The solution to this equation could not be determined.
| x-1/2x+14-x+5/9x+63 | | Ln(200)=ln(27x)+0.2x | | m+22=21 | | (2w^3-9w^5+2)10w^4= | | 2x+1=3y | | 8x^4(2-5x^2)= | | 180=12*x | | 6w^3(9w^7+4w)= | | 13=2*3.14*x | | (7/6n)+(1/2n)=5 | | 10.99=2*3.14*x | | 3x+6y=-2 | | 37.7=2*3.14*x | | 9x/2=49.5 | | x^2+x+5=65 | | 14x=49.5 | | (2w^2-7w^4+7)3w^5= | | 7x/2=49.5 | | 9w^2-9=0 | | 6y^2(10-9y^3)= | | 9(2x+5)=6(x-2)-3 | | 15*1.20= | | x^4+b*x^2+c=0 | | 2.40(1.20*15)= | | 5*x^3-x^2=0 | | 9(t-5)+5t=7(2t+5)-9 | | (x-3)(x+3)+(x-3)(x+8)= | | x+2y+5=0 | | 8a-6b=12 | | 3x^2-10x=-13x | | (-2)(-3)(5)(4)= | | 0.6(0.2)= |